Marketing communications : integrating online and offline, customer engagement and digital technologies - Smith, P. R. (Paul Russell), 1957-; Zook, Ze (KoganPage, 2024)
"The integration of online and offline marketing techniques is central to modern marketing practice. Companies can no longer compete if their digital and traditional marketing operate in silos, and organisations are therefore looking for graduates with the skills to implement genuinely integrated marketing campaigns. This new edition of Marketing Communications has had, from its very first edition, a strong focus on integration, and will give students the precise skills that employers are seeking. This new, seventh edition is written by both an academic and professional, and therefore provides the perfect balance of research and theory combined with real world practicality that teaches students the why behind the how. Marketing Communications features a mixture of extended and short case studies, giving lecturers the flexibility to choose what best suits their teaching style. With increased focus on social media as well as coverage of the latest digital technologies, students will learn more than just how to use the current preferred digital marketing tools - they will become truly confident working in an environment of ongoing technological transformation. Online resources include chapter slides, multiple choice question bank, and video reviews"--